Design, construction and operation of solar dryer for granules and micros chips of Manihot esculenta crantz tuberous roots - Efoto, P.B.; Eale, L.E.; Singl, S.L.; Meso, M.N. (International Association for Sharing Knowledge and Sustainability, 2015)
This study presents the design details and the performance analyses carried out with Eloumah 1, the solar drier of cassava tuberous roots reduced in granules and microchips. Eloumah 1 is composed by a solar collector, a drying chamber and a box of rectangular section that joins the two previous components. In this solar drier the wet agricultural products are dried on the basis of the heat flux buoyancy that is induced by the difference in temperature and humidity in its compartments. Analyses of masses evaporated water of zizila and Obama (TME 419) granules and microchips tuberous roots varieties have been carried out in order to estimate the drying performance of Eloumah 1 and to know the natural laws of the drying process. The results show that Eloumah 1 is able to dry granules and microchiphs and to reduce their moisture contain to less than 10%. Moreover, it can be established that the drying process is a logistic process because in wet control samples, moisture contain has limited value. Therefore, the drying process cannot extract the free water beyond this limit value. The logistic function adjusts well these data based on the correlation coefficient (R2) and chi square coefficient (?2).